PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KOGNITIF DAN MOTIVASI BELAJAR IPA - Dede Kusnandar (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
This research is motivated by the low student learning outcomes in the Natural Sciences subject matter of the Earth and disasters. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on cognitive learning outcomes in the Earth and Disaster Layer material and the influence of the PBL model on learning motivation in the Earth and Disaster Layer material. The research method used in this study is a quasi-experimental method. Data collection techniques using questionnaire techniques, documentation studies, and literature studies. Data analysis using simple regression test and multiple regression test. The population used in this study were all VII grade students of MTs Legokjawa 2018/2019 academic year totaling three classes. The sample is taken by simple random sampling technique. Class VII-A as the control class and class VII-B as the experimental class. The results showed that the results of the t test test t value of 5.598 obtained significance in the equal variances assumed column of 0,000, which means that there was an influence PBL learning model on motivation in earth layer material and disasters, and the t test results of 2,897 obtained significance in the column equal variances assumed is 0.006, which means that there is an influence of the PBL model on cognitive learning outcomes in earth layer material and disasters.